Florid Cementoosseous Dysplasia: A Rare Case Report - Mehmet Fatih Şentürk; Recep Kestane; Elif Naz Yakar; Ahmet Keskin (Hindawi Limited, 2013)
Florid cementoosseous dysplasia (FCOD) is a rare, benign, fibroosseous, and multifocal dysplastic lesion of the jaw that consists of cellular fibrous connective tissue with bone and cementum-like tissue. FCOD is most commonly found in middle-aged black women, is generally asymptomatic, and is usually detected during radiological examination. FCOD associated with multiple impacted teeth and bone expansion is a very rare phenomenon, and there are only a few familial cases reported in the literature. In this report, a 35-year-old male Turkish patient is presented who was diagnosed with nonfamilial FCOD from clinical, radiological, and histopathological findings. To our knowledge this is the first case of the nonfamilial FCOD with this many impacted teeth and severely expanded bones.